Input coupling systems for millimetre‐wave gyrotron travelling wave amplifiers. Issue 11 (24th April 2018) - Zhang, Liang; Donaldson, Craig R.; Garner, Jason; Cross, Adrian W.; He, Wenlong
Abstract : Input couplers for millimetre‐wave gyrotron travelling wave amplifiers are presented in this study. A W‐band input coupling system composed of a pillbox window, a smoothly curved waveguide bend, a T‐junction and a broadband reflector was numerically optimised, constructed and measured. An average transmission coefficient of −2.0 dB over a designed operating frequency range was measured. Additionally, a higher‐frequency input coupler for operation at a central frequency of 372 GHz was also designed based on a multiple‐hole coupling configuration. The simulated transmission coefficient was −0.5 dB if the ohmic loss is not considered.